Financial and Economic Crises as an Instrument of Realization of the USA Geopolitical Interests - G Yu Filimonov; S A Tsaturyan (Vestnik RUDN. International Relations, 2012)
The article deals with financial and economic crisis, projected by American financial aristocracy to optimize global processes management. Here is the analysis of the way crisis effects global agenda. The article also describes the history of the US Federal Reserve creation and the US economic influence upon the world order. The authors declare that crisis reinforces US role in modern world policy and weakens national governments depending on US dollar incomes.